Questionnaire for Children with Autism Syndrome Disorder - Suprajitno Suprajitno; Sri Mugianti (STIKes Patria Husada Blitar in collaboration with PPNI Kabupaten blitar, 2021)
Children with autism syndrome disorder  (ASD) have developmental like normal children in general. However, in Indonesia there is no instrument to measure of achievement the development of children with autism syndrome disorder. The purpose of this research resulted in a questionnaire used to measure institutional and family support, parental stimulation abilities, and the ability of children with autism syndrome disorder. The design used exploratory for developing of instruments. Experts involved in the development of instruments are psychologists, occupational therapists, speech therapists, paediatricians, autistic child behavioral therapy practitioners, and the institution of Autism Center of Blitar City. Instrument development begins with focus group discussion, instrument preparation, instrument trials, and analysis. The questionnaire trial was conducted on 40 parents and children with ASD at the Autism Center of Blitar City. The analysis was conducted namely the validity of the content and construct by experts, while the test of validity and reliability of the questionnaire used Lisrel 8.50. Valid and reliable questionnaires items on the institutional and family support as many as 21 questions, parents' ability to stimulate as many as 17 questions, and the ability of children with autism syndrome disorder as many as 17 questions. The resulting questionnaire has a minimum GFI score of 0.75 and a CR of 0.78, so that the questionnaire can be used as a instrument on autism services.